Saving the reservation : Joe Garry and the battle to be Indian - Fahey, John, 1919-2004 (Book collections on Project MUSE., 2001)
"Joseph R. Garry (1910-1975), a Coeur d'Alene Indian, served six terms as president of the National Congress of American Indians in the 1950s. He led the battles to compel the federal government to honor treaties and landownership and dominated an era in government-Indian relations little attended by historians. Firmly believing that forced assimilation of Indians and termination of federal trusteeship over Native Americans and their reservations would doom Indian cultures, Garry had his greatest success as a leader in uniting American Indian tribes to fend off Congress's plan to abandon Indian citizens."--Jacket